Current status and research trends of textile wastewater treatments—A bibliometric-based study - Halepoto, Habiba; Gong, Tao; Memon, Hafeezullah (Frontiers in Environmental Science, 2022)
While introducing new technology has completely transformed the textile production process, the rapid pace of massive industrialization has increased the volume of wastewater, which is highly hazardous. Even though the textile industry is essential to our economy, the textile industry is harmful to the environment because of the production of wastewater, solid wastes, air pollutants, noise, etc. Recycling textile wastewater is crucial, and oxidation, physical, biological, and physicochemical methods can be used to treat textile wastewater. Based on statistics and visualization tools, bibliometric analysis has evolved to demonstrate a given topic's knowledge structures and developmental tendencies. Here we provide a bibliometric analysis focused on textile wastewater treatment from 1990 to 2022. Raw data was retrieved from the Web of Science (WoS) database and mapped using VOSviewer and biblioshiny. Textile, wastewater, and treatment were keywords. We retrieved 8170 documents, 1138 sources published these documents, a 22.7% annual increase, where 21458 authors published these documents with an average citation rate of 33.2%, and there were 6680 research articles and 462 review articles. DESALINATION AND WATER TREATMENT stayed on top with 422 publications. We discovered that DONGHUA UNIVERSITY ranks first with 330 publications. Though China took first place with a total of 43961 citations, followed by India with a total of 33953 citations, from a total of 120 countries participating in this research, the research work of CRINI G and coworkers was most cited globally. The most common term was wastewater, which occurred 3144 times, followed by textile, which appeared 2669 times. We expect this research to be a significant resource for scholars by comprehensively describing the current state and future directions of textile wastewater treatment.